Lactobacillus casei Encapsulated in Soy Protein Isolate and Alginate Microparticles Prepared by Spray Drying - Hadzieva, Jasmina; Mladenovska, Kristina; Crcarevska, Maja Simonoska; Dodov, Marija Glavaš; Dimchevska, Simona; Geškovski, Nikola; Grozdanov, Anita; Popovski, Emil; Petruševski, Gjorgji; Chachorovska, Marina; Ivanovska, Tanja Petreska; Petruševska-Tozi, Lidija; et al. (Faculty of Food Technology and Biotechnology - University of Zagreb, 2017)
This article presents a novel formulation for preparation of Lactobacillus casei 01 encapsulated in soy protein isolate and alginate microparticles using spray drying method. A response surface methodology was used to optimise the formulation and the central composite face-centered design was applied to study the effects of critical material attributes and process parameters on viability of the probiotic after microencapsulation and in simulated gastrointestinal conditions. Spherical microparticles were produced in high yield (64%), narrow size distribution (d50=9.7 µm, span=0.47) and favourable mucoadhesive properties, with viability of the probiotic of 11.67, 10.05, 9.47 and 9.20 log CFU/g after microencapsulation, 3 h in simulated gastric and intestinal conditions and four-month cold storage, respectively. Fourier-transform infrared spectroscopy confirmed the probiotic stability after microencapsulation, while differential scanning calorimetry and thermogravimetry pointed to high thermal stability of the soy protein isolate-alginate microparticles with encapsulated probiotic. These favourable properties of the probiotic microparticles make them suitable for incorporation into functional food or pharmaceutical products.